Peran pendidikan karakter dalam membentuk generasi unggul di era globalisasi - Amalya, Habiba Tazkia (Maliki Interdisciplinary Journal, 2026)
Character education plays a crucial role in the formation of a high-quality generation. This study aims to analyze the role of character education in shaping individuals who are not only intellectually competent but also prossess strong moral values and social responsibility. In the context of modern education, the emphasis on cognitive achievement often overshadows the importance of caracter development, leading to various moral and social issues. Therefore, integrating character education into the educational system becomes essential. The findings indicate thet character education contributes significantly to the development of integrity, discipline, responsibility, and leadership qualities. These attributes are fundamental in creating individuals who are capable of adapting to social changes and contributing positively to society. However, the implementation of character education faces several challenges, including the influence of globalization, technological advancement, and the lack of consistent role modelsin both educational institution and scienty. To address these cahllenges, collaboration among educators, families, and communities is necessary. In conclusion, character education is a vital component in developing a superior generation with balanced intellectual and moral competencies.